Fermentasi Ampas Tahu Menjadi Tempe Gembus Pada Pabrik Pak Sugeng - Putri , Indi Desti Dwi (Jurnal Kewirausahaan dan Bisnis, 2024)
Tempe gembus is one of Indonesia's original fermented food products, which is obtained from the fermentation process of tofu pulp with Rhizopus spp. Tempe gembus is made from the overflow of tofu making, namely tofu pulp. Generally, tofu dregs are used as animal feed, but it turns out that the fermentation process of tofu dregs with Rhizopus spp. into tempeh has nutritional content of tempeh gembus, including unsaturated fats, carbohydrates, and proteins. Tempe gembus also contains bioactive isoflavone compounds, peptides that have antioxidant activity. Tempe gembus is a native Indonesian food made from the overflow of tofu making (tofu pulp) fermented using Rhizopus oligosporus fungus. The name gembus describes the physical state of tempeh/tempe texture which in Javanese means soft but has a fixed shape. Tempe gembus is widely consumed by the people of Central Java and Yogyakarta.